Negative electrode material, negative electrode plate containing negative electrode material and battery

By providing a cladding layer containing fluorine and nitrogen elements on the surface of the silicon-based material, the problem of volume expansion of the silicon-based material during fast charging is solved, and the rate performance and fast charging cycle stability of the battery are improved.

CN119725451AActive Publication Date: 2025-03-28EVE ENERGY CO LTD

Patent Information

Application Number
CN202411901439.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-28
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

Silicon-based materials are prone to huge volume expansion during fast charging, resulting in the breakage of active substance particles, peeling off the active coating, and destroying the conductive network, affecting the fast charging performance and cycle life of the battery.

Method used

By sequentially providing a first cladding layer of fluorine-containing element and a second cladding layer of nitrogen-containing element on the surface of the silicon-based material, the mass proportion of fluorine-containing element and nitrogen-containing element is regulated, the conductivity, structural stability and flexibility of the negative electrode material are improved, and the expansion problem of silicon-based material is alleviated.

Benefits of technology

It improves the battery's rate performance and fast charging cycle stability, and extends the battery's fast charging cycle life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
  • Figure QLYQS_3
    Figure QLYQS_3
Patent Text Reader

Abstract

The invention provides a negative electrode material, a negative plate containing the negative electrode material and a battery. The negative electrode material comprises a silicon-based material, a first coating layer and a second coating layer, wherein the first coating layer and the second coating layer are sequentially arranged on the surface of the silicon-based material; the first coating layer contains a fluorine element; the second coating layer contains a nitrogen element; the mass ratio of the fluorine element in the first coating layer is 1-3%; and the mass ratio of the nitrogen element in the second coating layer is 1-4%. According to the negative electrode material provided by the invention, the surface of the silicon-based material is sequentially coated with the first coating layer containing the fluorine element and the second coating layer containing the nitrogen element, so that the rate capability and the fast charge cycle stability of a battery applying the negative electrode material can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a negative electrode material, a negative electrode sheet containing the negative electrode material, and a battery. Background Art

[0002] In order to solve the problem of long charging time for new energy vehicles, the development of fast charging technology has become one of the main directions of the industry. In this context, the use of high-rate charging for vehicle power batteries has become a trend in market applications. High-rate charging can reduce the time required for charging, so the research on high-rate power batteries has become a key factor in promoting the development of the industry.

[0003] At present, commercial fast charging is mainly concentrated on the graphite system, but when graphite negative electrode materials are directly used in fast-charging batteries, there is a disadvantage of low battery energy density.

[0004] Silicon-based material is a new type of battery negative electrode material with a higher theoretical specific capacity than traditional graphite negative electrode (up to 4200mAh / g, more than 10 times that of graphite). In addition, silicon-based material also has the advantages of low discharge platform, high charge and discharge efficiency, and good safety. It can improve the energy density and cruising range of the battery and is an ideal choice for the new generation of high energy density batteries.

[0005] However, silicon-based materials are prone to huge volume expansion during the fast charging process, with volume changes as high as 300%. This can cause a series of failure problems such as breakage of active material particles, peeling of active coatings, and destruction of conductive networks. This is not conducive to the fast charging performance of the battery and also seriously affects the fast charging cycle life of the battery. Summary of the invention

[0006] In order to solve the problem that the existing silicon-based materials undergo huge volume expansion during fast charging and affect the fast charging performance of the battery using the same, the present invention provides a negative electrode material, a negative electrode sheet containing the same and a battery.

[0007] According to a first aspect of the present invention, a negative electrode material is provided, which includes a silicon-based material and a first coating layer and a second coating layer sequentially arranged on the surface of the silicon-based material; the first coating layer contains fluorine element; the second coating layer contains nitrogen element; the mass proportion of fluorine element in the first coating layer is 1 to 3%; the mass proportion of nitrogen element in the second coating layer is 1 to 4%.

[0008] In the negative electrode material provided by the present invention, a first coating layer containing fluorine and a second coating layer containing nitrogen are sequentially coated on the surface of a silicon-based material, and the content of fluorine in the first coating layer and the content of nitrogen in the second coating layer are regulated, and the negative electrode material is applied to a negative electrode sheet and a battery. First, since the electronic conductivity of the silicon-based material itself is relatively low, the first coating layer and the second coating layer are arranged on the surface of the silicon-based material, which can improve the conductivity of the negative electrode material with the silicon-based material as the main body, thereby improving the electrochemical performance and rate performance of the battery. Second, fluorine is doped in the first coating layer, and the fluorine element can form hydrogen bonds with the hydroxyl groups on the surface of the silicon-based material. The presence of hydrogen bonds is conducive to enhancing the structural stability and flexibility of the negative electrode material, so that the negative electrode material can more stably withstand the volume change of the silicon-based material during the lithium ion insertion and extraction process, thereby achieving better fast charging cycle stability performance and improving the fast charging cycle life of the battery. Third, nitrogen is doped in the second coating layer, which can alleviate the expansion of the silicon-based material during the fast charging process and improve the fast charging cycle stability. In summary, the negative electrode material provided by the present invention can improve the rate performance and fast charging cycle stability of the battery using the negative electrode material by sequentially coating the surface of the silicon-based material with a first coating layer containing fluorine elements and a second coating layer containing nitrogen elements.

[0009] If the mass proportion of fluorine element in the first coating layer is too small, the hydrogen bond force between fluorine element and silicon-based material is too weak and the coating effect is poor. If the mass proportion of fluorine element in the first coating layer is too large, the ion transmission distance will be increased, resulting in a decrease in the rate performance of the battery. If the mass proportion of nitrogen element in the second coating layer is too small, it will be difficult to improve the rate performance of the battery and the stability of the negative electrode surface structure. If the mass proportion of nitrogen element in the second coating layer is too large, the ion transmission distance will be increased, thereby reducing the rate performance of the battery.

[0010] Preferably, the first coating layer comprises a first polymer, the first polymer comprising a single monomer as shown in Formula I;

[0011]

[0012] R1, R2, R3, and R4 are independently selected from —H, alkyl, and —F, and at least one of R1, R2, R3, and R4 is —F.

[0013] Preferably, the second coating layer contains a second polymer, and the second polymer includes a second monomer as shown in Formula II;

[0014]

[0015] X contains a urea group.

[0016] The second coating layer of the negative electrode material involved in this scheme contains a polar group urea. On the one hand, the urea group increases the transmission speed of lithium ions through physical interaction with lithium ions, thereby improving the rate performance of the battery using the negative electrode material. On the other hand, the urea group can form a strong hydrogen bond with Li2O, Li2CO3, LiF, etc. in the SEI film formed on the surface of the negative electrode, which is beneficial to improve the structural stability of the negative electrode surface and further improve the fast charging cycle stability of the battery.

[0017] Preferably, the first polymer comprises a first monomer as shown in Formula III;

[0018]

[0019] Preferably, the second polymer comprises a second monomer as shown in Formula IV;

[0020]

[0021] Preferably, the number average molecular weight of the first polymer is 30,000-100,000.

[0022] Preferably, the number average molecular weight of the second polymer is 10,000-80,000.

[0023] The number average molecular weights of the first polymer used to form the first coating layer and the second polymer used to form the second coating layer are controlled within the above range. Firstly, the bonding strength between the first coating layer and the second coating layer can be maintained within an appropriate range, which is beneficial to reducing the risk of the first coating layer and the second coating layer falling off or peeling off during multiple cycles of charge and discharge of the negative electrode material. Secondly, the first coating layer and the second coating layer have good mechanical strength, which can improve the buffering effect of the first coating layer and the second coating layer on the volume expansion of the silicon-based material during the charge and discharge of the negative electrode material. Thirdly, the first coating layer and the second coating layer have good uniformity and density, which can improve the cycle stability of the negative electrode material during the charge and discharge process.

[0024] If the number average molecular weight of the first polymer used to form the first coating layer and the second polymer used to form the second coating layer is too small, the bonding strength between the first coating layer and the second coating layer will be low, and the first coating layer and the second coating layer will easily fall off or peel off during the charge and discharge cycle, and the mechanical strength will be low; if the number average molecular weight of the second polymer used to form the second coating layer is too large, the difficulty of coating will be increased, and the uniformity and density of the first coating layer and the second coating layer will also be affected.

[0025] Preferably, the mass proportion of the first coating layer in the negative electrode material is 2-4%.

[0026] Preferably, the thickness of the first coating layer is 3-80 nm.

[0027] Preferably, the mass proportion of the second coating layer in the negative electrode material is 1-5%.

[0028] Preferably, the thickness of the second coating layer is 2-100 nm.

[0029] Controlling the mass ratio and thickness of the first coating layer and the second coating layer within the above range can improve the lithium ion transmission performance, rate performance and cycle performance of the negative electrode material, and the first coating layer and the second coating layer have good flexibility.

[0030] If the mass ratio of the first coating layer and the second coating layer is too small and the thickness is too thin, the first coating layer and the second coating layer are easy to break during multiple cycles of charge and discharge, thereby causing loss of active lithium; if the mass ratio of the first coating layer and the second coating layer is too large and the thickness is too thick, the ion transport performance of the negative electrode material will be poor, resulting in a decrease in its rate performance and cycle performance.

[0031] Preferably, the particle size D50 of the negative electrode material is 6 to 10 μm.

[0032] Controlling the particle size D50 of the negative electrode material within the above range can not only keep the lithium ion transmission path within an appropriate range, but also ensure the compaction density of the negative electrode sheet made using the negative electrode material and the energy density of the battery.

[0033] Preferably, the specific surface area of ​​the negative electrode material is 1 to 7 m 2 / g.

[0034] Preferably, the silicon content in the silicon-based material is 20-80 wt%.

[0035] Controlling the silicon content of the silicon-based material in the negative electrode material within the above range and applying it to the negative electrode sheet and the battery can not only ensure the energy density and rate performance of the battery, but also avoid the risk of excessive silicon content causing excessive volume expansion of the silicon-based material during charging and discharging, which may lead to rupture of the negative electrode material.

[0036] If the silicon content of the silicon-based material in the negative electrode material is too high, the silicon-based material will expand too much during the charge and discharge process, and will be more prone to the risk of rupture; if the silicon content of the silicon-based material in the negative electrode material is too low, the energy density and rate performance of the battery using it will decrease.

[0037] Preferably, the silicon-based material includes at least one of silicon monoxide (SiO) and silicon carbon material (SiC).

[0038] Preferably, in the internal pores and external pores of silicon carbon, the proportion of mesopores is 42-87%, and the proportion of micropores is less than 59%, wherein the diameter of the mesopores is 3-42 nm, and the diameter of the micropores is 0.6-2 nm.

[0039] Preferably, the above negative electrode material is prepared by the following steps:

[0040] S1. After mixing the fluorine source and the silicon-based material, ball milling is performed at 230 to 400 ° C for 5 to 20 hours to obtain a silicon-based material containing a first coating layer;

[0041] S2. preparing a nitrogen source solution using a nitrogen source and an organic solvent;

[0042] S3. Applying a nitrogen source solution to the surface of the silicon-based material containing the first coating layer, and drying the nitrogen source solution to form a second coating layer on the surface of the silicon-based material containing the first coating layer, thereby obtaining a negative electrode material.

[0043] Preferably, S1 comprises the following operations: mixing a fluorine source with a silicon-based material and ball milling the mixture at 230-400° C. for 5-20 hours to obtain a silicon-based material containing a first coating layer.

[0044] Preferably, in S2, the organic solvent includes at least one of benzene, N-methylpyrrolidone (NMP) and N,N-dimethylformamide (DMF).

[0045] Preferably, in S2, the mass fraction of the nitrogen source solution is 3-25%.

[0046] Preferably, S3 includes the following operations: mixing the silicon-based material containing the first coating layer with the nitrogen source solution and stirring at 30-80° C. for 4-10 hours to obtain a mixed solution, and spray-drying the mixed solution to obtain a negative electrode material.

[0047] Preferably, the inlet temperature of the spray drying is 100-200°C, and the outlet temperature is 60-90°C.

[0048] According to a second aspect of the present invention, a negative electrode sheet is provided, the negative electrode sheet comprising the negative electrode material described above.

[0049] According to a third aspect of the present invention, a battery is provided, the battery comprising the above-mentioned negative electrode sheet.

[0050] The negative electrode material provided by the present invention is applied to negative electrode sheets and batteries, which can give the batteries excellent rate performance and fast charging cycle stability. DETAILED DESCRIPTION

[0051] The following is a further clear and complete description of the technical features in the technical solution provided by the present invention in conjunction with the specific implementation methods. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0052] Example 1

[0053] A battery is prepared by the following steps:

[0054] 1. Preparation of negative electrode

[0055] The negative electrode material, conductive carbon black (SP), single-walled carbon nanotube (SWCNT), and binder polyacrylic acid (PAA) were mixed in a mass ratio of 80:9:1:10 and added into a solvent deionized water, and mixed evenly to prepare a negative electrode slurry with a solid content of 30%. The negative electrode slurry was coated on both surfaces of the negative electrode current collector copper foil to form a negative electrode active coating, and after vacuum drying and cold pressing, a negative electrode sheet was prepared;

[0056] The negative electrode material comprises a silicon material and a first coating layer and a second coating layer sequentially arranged on the surface of the silicon-based material, the first coating layer comprises a first polymer, the first polymer comprises a first monomer as shown in formula III, the second coating layer comprises a second polymer, the second polymer comprises a second monomer as shown in formula IV;

[0057]

[0058]

[0059] The above negative electrode material is prepared by the following steps:

[0060] S1. After mixing the fluorine source (first polymer) and the silicon-based material, ball milling was performed at 300° C. for 12 h to obtain a silicon-based material containing a first coating layer;

[0061] The fluorine source is prepared by the following steps: adding the first monomer into an organic solvent NMP, adding an initiator azobisisobutyronitrile, heating to 65° C. under nitrogen protection for 7 hours to obtain a first polymer with a number average molecular weight of 50,000 to 55,000;

[0062] The silicon-based material involved in this embodiment is silicon-carbon material;

[0063] S2. A nitrogen source solution having a mass fraction of 15% is prepared by using a nitrogen source (a second polymer) and an organic solvent NMP;

[0064] The nitrogen source is prepared by the following steps: adding the second monomer to an organic solvent NMP, adding an initiator azobisisobutyronitrile, heating to 70° C. under nitrogen protection for 10 hours to obtain a second polymer with a number average molecular weight of 50,000 to 55,000;

[0065] S3. The silicon-based material containing the first coating layer is mixed with the nitrogen source solution and stirred at 55°C for 7h to obtain a mixed solution, and the mixed solution is spray-dried to form a second coating layer on the surface of the silicon-based material containing the first coating layer to obtain a negative electrode material having a particle size D50 of 8 μm, wherein the inlet temperature of the spray drying is 150°C and the outlet temperature is 75°C;

[0066] The thickness of the first coating layer is 40 nm, the thickness of the second coating layer is 55 nm, the mass proportion of the fluorine element in the first coating layer is 2.5%, and the mass proportion of the nitrogen element in the second coating layer is 2.5%.

[0067] 2. Preparation of positive electrode

[0068] The positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2, conductive carbon black (SP) and binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 96:2:2 and added to a solvent N-methylpyrrolidone (NMP). The mixture is evenly mixed to obtain a positive electrode slurry with a solid content of 45%. The positive electrode slurry is coated on both surfaces of the positive electrode current collector aluminum foil to form a positive electrode active coating. After vacuum drying and cold pressing, a positive electrode sheet is obtained.

[0069] 3. Preparation of Diaphragm

[0070] A polyethylene (PE) film containing a ceramic layer is used as the diaphragm.

[0071] 4. Preparation of Electrolyte

[0072] Ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and fluoroethylene carbonate (FEC) are mixed in a mass ratio of 20:40:30:10 to obtain an organic solvent, and then fully dried lithium salt LiPF6 is dissolved in the organic solvent to prepare an electrolyte with a concentration of 1M.

[0073] 5. Battery Assembly

[0074] The positive electrode sheet, separator and negative electrode sheet are stacked in order, so that the separator is placed between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell, which is placed in an outer packaging shell, dried and injected with the above-mentioned electrolyte, and subjected to vacuum packaging, standing, forming, shaping and other processes to obtain a battery.

[0075] Example 2

[0076] This embodiment provides a battery. Compared with the embodiment 1, the difference in structure is that the preparation method of the negative electrode material used in the negative electrode sheet is different.

[0077] The negative electrode material used in this embodiment is prepared by the following steps:

[0078] The above negative electrode material is prepared by the following steps:

[0079] S1. After mixing the fluorine source and the silicon-based material, ball milling was carried out at 230°C for 20 hours to obtain a silicon-based material containing a first coating layer;

[0080] The fluorine source is a first polymer having a number average molecular weight of 30,000 to 35,000;

[0081] S2. A nitrogen source solution having a mass fraction of 3% was prepared by using a nitrogen source and an organic solvent NMP;

[0082] Wherein, the nitrogen source is a second polymer having a number average molecular weight of 10,000 to 15,000;

[0083] S3. The silicon-based material containing the first coating layer is mixed with the nitrogen source solution and stirred at 30°C for 10 hours to obtain a mixed solution, and the mixed solution is spray-dried to form a second coating layer on the surface of the silicon-based material containing the first coating layer to obtain a negative electrode material having a particle size D50 of 6 μm, wherein the inlet temperature of the spray drying is 100°C and the outlet temperature is 60°C;

[0084] The thickness of the first coating layer is 3 nm, the thickness of the second coating layer is 100 nm, the mass proportion of fluorine element in the first coating layer is 1.3%, and the mass proportion of nitrogen element in the second coating layer is 1.4%.

[0085] Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.

[0086] Example 3

[0087] This embodiment provides a battery. Compared with the embodiment 1, the difference in structure is that the preparation method of the negative electrode material used in the negative electrode sheet is different.

[0088] The negative electrode material used in this embodiment is prepared by the following steps:

[0089] The above negative electrode material is prepared by the following steps:

[0090] S1. After mixing the fluorine source and the silicon-based material, ball milling was performed at 400 ° C for 5 h to obtain a silicon-based material containing a first coating layer;

[0091] The fluorine source is a first polymer having a number average molecular weight of 95,000 to 100,000;

[0092] S2. A nitrogen source solution having a mass fraction of 25% was prepared by using a nitrogen source and an organic solvent NMP;

[0093] The nitrogen source is a second polymer having a number average molecular weight of 75,000 to 80,000;

[0094] S3. The silicon-based material containing the first coating layer is mixed with the nitrogen source solution and stirred at 80°C for 4h to obtain a mixed solution, and the mixed solution is spray-dried to form a second coating layer on the surface of the silicon-based material containing the first coating layer to obtain a negative electrode material having a particle size D50 of 10 μm, wherein the inlet temperature of the spray drying is 200°C and the outlet temperature is 90°C;

[0095] The thickness of the first coating layer is 80 nm, the thickness of the second coating layer is 2 nm, the mass proportion of fluorine element in the first coating layer is 2.8%, and the mass proportion of nitrogen element in the second coating layer is 3.5%.

[0096] Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.

[0097] Example 4

[0098] This embodiment provides a battery, and compared with the embodiment 1, the difference in structure is that the first polymer contained in the first coating layer of the negative electrode material is different, and the first monomer used is as shown in formula V;

[0099]

[0100] Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.

[0101] Example 5

[0102] This embodiment provides a battery, which is different from that of embodiment 1 in that the second coating layer in the negative electrode material contains a different second polymer, and the second monomer used is as shown in formula VI;

[0103]

[0104] Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.

[0105] Example 6

[0106] This embodiment provides a battery, which is different from that of embodiment 1 in that the second coating layer in the negative electrode material contains a different second polymer, and the second monomer used is as shown in formula VII;

[0107]

[0108] Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.

[0109] Example 7

[0110] The present embodiment provides a battery, which has the following differences compared with the embodiment 1: (1) in the step S1 of preparing the negative electrode material, the first monomer is added to the organic solvent NMP, the initiator azobisisobutyronitrile is added, and the mixture is heated to 40°C for reaction for 3 hours under nitrogen protection to obtain a first polymer with a number average molecular weight of 20,000 to 25,000 as a fluorine source; (2) in the step S2 of preparing the negative electrode material, the second monomer is added to the organic solvent NMP, the initiator azobisisobutyronitrile is added, and the mixture is heated to 40°C for reaction for 5 hours under nitrogen protection to obtain a second polymer with a number average molecular weight of 8,000 to 8,500 as a nitrogen source.

[0111] Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.

[0112] Example 8

[0113] The present embodiment provides a battery, which has the following differences compared with the embodiment 1: (1) in the step S1 of preparing the negative electrode material, the first monomer is added to the organic solvent NMP, the initiator azobisisobutyronitrile is added, and the mixture is heated to 95° C. for reaction for 12 h under nitrogen protection to obtain a first polymer with a number average molecular weight of 110,000 to 115,000 as a fluorine source; (2) in the step S2 of preparing the negative electrode material, the second monomer is added to the organic solvent NMP, the initiator azobisisobutyronitrile is added, and the mixture is heated to 100° C. for reaction for 10 h under nitrogen protection to obtain a second polymer with a number average molecular weight of 90,000 to 95,000 as a nitrogen source.

[0114] Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.

[0115] Example 9

[0116] This embodiment provides a battery. Compared with the embodiment 1, the difference in structure is that the thickness of the first coating layer of the negative electrode material is 2 nm, and the thickness of the second coating layer is 120 nm.

[0117] Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.

[0118] Example 10

[0119] This embodiment provides a battery. Compared with the embodiment 1, the difference in structure is that the thickness of the first coating layer of the negative electrode material is 90 nm, and the thickness of the second coating layer is 1 nm.

[0120] Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.

[0121] Embodiment 11

[0122] This embodiment provides a battery. Compared with the embodiment 1, the difference in structure is that in the negative electrode material preparation step S3, the particle size of the negative electrode material prepared is 4 μm.

[0123] Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.

[0124] Example 12

[0125] This embodiment provides a battery. Compared with the embodiment 1, the difference in structure is that in the step S3 of preparing the negative electrode material, the particle size of the prepared negative electrode material is 13 μm.

[0126] Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.

[0127] Comparative Example 1

[0128] This comparative example provides a battery. Compared with Example 1, the difference in structure is that the negative electrode material used in the preparation process of the negative electrode sheet is a silicon-based material without the first coating layer and the second coating layer.

[0129] Except for the above differences, the materials, formula ratios and preparation operations used in this comparative example are strictly consistent with those in Example 1.

[0130] Comparative Example 2

[0131] This comparative example provides a battery, and compared with Example 1, the difference in structure is that the negative electrode material used in the preparation process of the negative electrode sheet is a silicon-based material without a first coating layer and only containing a second coating layer, and the thickness of the second coating layer is 95nm.

[0132] Except for the above differences, the materials, formula ratios and preparation operations used in this comparative example are strictly consistent with those in Example 1.

[0133] Comparative Example 3

[0134] This comparative example provides a battery, and compared with Example 1, the difference in structure is that the negative electrode material used in the preparation process of the negative electrode sheet is a silicon-based material without a second coating layer and only containing a first coating layer, and the thickness of the first coating layer is 95nm.

[0135] Except for the above differences, the materials, formula ratios and preparation operations used in this comparative example are strictly consistent with those in Example 1.

[0136] Comparative Example 4

[0137] This comparative example provides a battery, which has the following differences in structure compared with Example 1: (1) in the negative electrode material preparation step S1, a fluorine source (first polymer) and a silicon-based material are mixed and then ball-milled at 300° C. for 29 hours to obtain a silicon-based material containing a first coating layer; (2) in the negative electrode material preparation step S2, a nitrogen source (second polymer) and an organic solvent NMP are used to prepare a nitrogen source solution with a mass fraction of 1.5%; (3) in the negative electrode material prepared in the negative electrode material preparation step S3, the mass fraction of fluorine element in the first coating layer is 4.5%, and the mass fraction of nitrogen element in the second coating layer is 0.2%.

[0138] Except for the above differences, the materials, formula ratios and preparation operations used in this comparative example are strictly consistent with those in Example 1.

[0139] Comparative Example 5

[0140] This comparative example provides a battery, which has the following differences in structure compared with Example 1: (1) in the preparation step S1 of the negative electrode material, the fluorine source (first polymer) and the silicon-based material are mixed and then ball-milled at 300° C. for 3 hours to obtain a silicon-based material containing a first coating layer; (2) in the preparation step S2 of the negative electrode material, a nitrogen source solution with a mass fraction of 29% is prepared by using a nitrogen source (second polymer) and an organic solvent NMP; (3) in the negative electrode material prepared in the preparation step S3 of the negative electrode material, the mass fraction of the fluorine element in the first coating layer is 0.8%, and the mass fraction of the nitrogen element in the second coating layer is 4.8%.

[0141] Except for the above differences, the materials, formula ratios and preparation operations used in this comparative example are strictly consistent with those in Example 1.

[0142] Comparative Example 6

[0143] This comparative example provides a battery, which has a different structure from that of Example 1 in that the first coating layer and the second coating layer of the negative electrode material contain different monomers;

[0144] The negative electrode material involved in this comparative example is prepared by the following steps:

[0145] S1. A nitrogen source solution having a mass fraction of 15% is prepared by using a nitrogen source and an organic solvent NMP;

[0146] The nitrogen source is prepared by the following steps: adding a monomer as shown in formula IV to an organic solvent NMP, adding an initiator azobisisobutyronitrile, heating to 70° C. under nitrogen protection for 10 hours to obtain a polymer with a number average molecular weight of 50,000 to 55,000 as a nitrogen source;

[0147] S2. The silicon-based material having a particle size D50 of 8 μm was mixed with the nitrogen source solution and stirred at 55 ° C for 7 h to obtain a mixed solution, and the mixed solution was spray-dried to form a first coating layer on the surface of the silicon-based material to obtain a silicon-based material containing a first coating layer;

[0148] S3. After mixing the fluorine source and the silicon-based material containing the first coating layer, ball milling was performed at 300 ° C for 12 h to form a second coating layer on the surface of the silicon-based material containing the first coating layer to obtain a negative electrode material;

[0149] The fluorine source is prepared by the following steps: adding a monomer as shown in formula III to an organic solvent NMP, adding an initiator azobisisobutyronitrile, heating to 65° C. under nitrogen protection for 7 hours to obtain a polymer with a number average molecular weight of 50,000 to 55,000 as a fluorine source;

[0150] The thickness of the first coating layer is 40 nm, the thickness of the second coating layer is 55 nm, the mass proportion of nitrogen in the first coating layer is 2.5%, and the mass proportion of fluorine in the second coating layer is 2.5%.

[0151] Except for the above differences, the materials, formula ratios and preparation operations used in this comparative example are strictly consistent with those in Example 1.

[0152] Test Case

[0153] 1. Participants

[0154] In this test example, the batteries prepared in Examples 1 to 12 and Comparative Examples 1 to 6 were used as test objects to conduct relevant performance tests.

[0155] 2. Test content

[0156] (1) First Coulomb efficiency

[0157] At 25°C, the battery was charged to 4.2V at a constant current and constant voltage rate of 0.33C, left to stand for 10 minutes, and then discharged to 2.5V at a constant current rate of 0.33C, left to stand for 10 minutes, and the first coulombic efficiency of the battery was calculated.

[0158] First coulombic efficiency (%) = total capacity of the battery at the first discharge at 0.33C / total capacity of the battery at the first charge at 0.33C × 100%.

[0159] (2) Capacity retention rate after 1200 cycles at 1C / 1C at room temperature

[0160] At 25°C, the battery was charged to 4.2V at a constant current and constant voltage rate of 1C, with a cut-off current of 0.05C, and allowed to stand for 10 minutes. Then, the battery was discharged to 2.5V at a constant current rate of 1C and allowed to stand for 10 minutes. This was considered a charge and discharge cycle. The battery was charged and discharged for 1200 cycles according to the above method, and the capacity retention rate after 1200 cycles of charge and discharge at 1C / 1C was calculated.

[0161] The capacity retention rate (%) of the battery after N cycles = (discharge capacity at the Nth cycle / first discharge capacity) × 100%, where N is the number of cycles of the battery.

[0162] (3) Room temperature 6C rate performance - constant current charging ratio

[0163] At 25°C, the battery was discharged at a constant current rate of 1C to 2.5V and allowed to stand for 10 minutes. Then, the battery was charged at a constant current and constant voltage rate of 6C to 4.2V with a cut-off current of 0.05C and allowed to stand for 10 minutes. The battery's 6C constant current charging capacity Q1, 6C constant current and constant voltage charging total capacity Q2 and the highest temperature during fast charging (i.e., the highest temperature of 6C rate charging) were recorded. The 6C rate charging constant current charging ratio was calculated according to the following formula: 6C rate charging constant current charging ratio = 6C constant current charging capacity Q1 / 6C constant current and constant voltage charging total capacity Q2 × 100%, wherein, constant current and constant voltage charging total capacity Q2 = constant current charging capacity + constant voltage charging capacity.

[0164] (4) 1C / 10C discharge capacity retention rate at room temperature

[0165] At 25°C, the divided battery is charged to 4.2V at a constant current and constant voltage rate of 1C, with a cut-off current of 0.05C. After standing for 10 minutes, the battery is discharged to 2.5V at a constant current rate of 1C, and its discharge capacity Q is recorded. 1C As the initial discharge capacity; then at 25 ° C, the battery was charged to 4.2V at a constant current and constant voltage rate of 1C, with a cut-off current of 0.05C, and left to stand for 10 minutes. Then, the fully charged battery was discharged to 2.5V at a constant current rate of 10C, and its discharge capacity Q was recorded. 10C ; Calculate the discharge capacity retention rate of the battery at 1C / 10C rate according to the following formula: Discharge capacity retention rate (%) = discharge capacity Q at 10C rate 10C / Discharge capacity at 1C rate Q 1C ×100%.

[0166] 3. Experimental results

[0167] Table 1. Test results of relevant performance of batteries

[0168]

[0169]

[0170] The relevant performance test results of the batteries prepared in Examples 1 to 12 and Comparative Examples 1 to 6 are shown in Table 1.

[0171] The negative electrode material used in the lithium battery provided in Comparative Example 1 is a silicon-based material without a coating layer, while the negative electrode material used in the batteries provided in Examples 1 to 12 includes a silicon-based material and a first fluorine-containing coating layer and a nitrogen-containing second coating layer sequentially arranged on the surface of the silicon-based material. The test results show that the first coulomb efficiency, the capacity retention rate of 1200 cycles of 1C / 1C cycle at room temperature, the constant current charging ratio of 6C rate charging and the discharge capacity retention rate of 1C / 10C at room temperature of the batteries provided in Examples 1 to 12 are significantly higher than those of Comparative Example 1. The above results indicate that by sequentially coating the surface of the silicon-based material with a first coating layer containing fluorine elements and a second coating layer containing nitrogen elements, the rate performance and fast charging cycle stability of the battery using it can be improved.

[0172] By comparing the test results of Examples 1, 4, 5, and 6, it can be shown that compared with the first monomer and the second monomer of other structures, the negative electrode material prepared by Example 1 using the first polymer formed by the polymerization reaction of the first monomer as shown in Formula III and the second polymer formed by the polymerization reaction of the second monomer as shown in Formula IV to coat the silicon-based material has better first coulombic efficiency, cycle performance, rate performance, and fast charging performance.

[0173] By comparing the test results of Examples 1, 7, and 8, it can be shown that by coating the silicon-based material with a first polymer having a number average molecular weight in the range of 30,000 to 100,000 and a second polymer having a number average molecular weight in the range of 10,000 to 80,000, the obtained negative electrode material and the battery using the same have better cycle performance and rate performance.

[0174] By comparing the test results of Example 1 and Comparative Examples 4 and 5, it can be seen that the fluorine content in the first coating layer of the negative electrode material and the nitrogen content in the second coating layer are controlled within the range of 1-3% and 1-4%, respectively, so that the rate performance and cycle performance of the prepared negative electrode material and the battery using the same can be better exerted.

[0175] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solutions of the present invention can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present invention.

Claims

1. A negative electrode material, characterized in that: The negative electrode material comprises a silicon-based material and a first coating layer and a second coating layer sequentially arranged on the surface of the silicon-based material; The first coating layer contains fluorine element; The second coating layer contains nitrogen; The mass proportion of the fluorine element in the first coating layer is 1-3%, and the mass proportion of the nitrogen element in the second coating layer is 1-4%.

2. The negative electrode material according to claim 1, characterized in that: The first coating layer contains a first polymer, the first polymer includes a single monomer as shown in formula I, and / or the second coating layer contains a second polymer, the second polymer includes a second monomer as shown in formula II; The R1, R2, R3, and R4 are independently selected from —H, alkyl, and —F, and at least one of the R1, R2, R3, and R4 is —F; The X contains a urea group.

3. The negative electrode material according to claim 2, characterized in that: The first polymer includes a first monomer as shown in Formula III, and / or the second polymer includes a second monomer as shown in Formula IV; 4. The negative electrode material according to claim 2, characterized in that: The number average molecular weight of the first polymer is 30,000 to 100,000, and / or the number average molecular weight of the second polymer is 10,000 to 80,000.

5. The negative electrode material according to claim 1, characterized in that: The mass proportion of the first coating layer in the negative electrode material is 2-4%, and / or the thickness of the first coating layer is 3-80 nm.

6. The negative electrode material according to claim 1, characterized in that: The mass proportion of the second coating layer in the negative electrode material is 1-5%, and / or the thickness of the second coating layer is 2-100 nm.

7. The negative electrode material according to claim 1, characterized in that: The particle size D50 of the negative electrode material is 6 to 10 μm.

8. The negative electrode material according to claim 1, characterized in that The negative electrode material is prepared by the following steps: S1. After mixing the fluorine source and the silicon-based material, ball milling at 230 to 400 ° C for 5 to 20 hours to obtain a silicon-based material containing the first coating layer; S2. preparing a nitrogen source solution using a nitrogen source and an organic solvent; S3. Applying the nitrogen source solution to the surface of the silicon-based material containing the first coating layer, drying the nitrogen source solution to form the second coating layer on the surface of the silicon-based material containing the first coating layer, and obtaining the negative electrode material.

9. A negative electrode sheet, characterized in that: The negative electrode sheet comprises the negative electrode material as claimed in any one of claims 1 to 8.

10. A battery, characterized in that: The battery comprises the negative electrode sheet as claimed in claim 9.

Citation Information

Patent Citations

  • Lithium ion battery negative pole active material and preparation method and application thereof

    CN104701489A

  • Silicon negative electrode material and preparation method therefor, negative electrode plate and lithium ion battery

    CN107302082A

  • Silicon negative electrode material coated with double-layer coating layer as well as preparation method and application thereof

    CN111540889A

  • Negative electrode material, negative electrode pole piece, secondary battery and electronic equipment

    CN118572072A

  • Silicon composite negative electrode material, negative electrode plate and battery

    CN119050294A

Cited By

  • Cylindrical battery monomer, battery device and power utilization device

    CN122393507A